Mitos Gugon Tuhon pada Serat Centhini 1 Gubahan Agus Wahyudi (Jurnal Pembelajaran Sastra, 2020)
Many people do not understand the various myths that live in society, including those that are explored in literary works. Serat Centhini I explores the myth of the gugon tuhon that still leaves questions. The purpose of this research is to explain the delivery of the myth of gugon tuhon in Serat Centhini 1 composed by Agus Wahyudi which includes (1) oral delivery and (2) delivery through reminders. This study uses a literary anthropological approach, an approach that reveals the cultural issues of gugon tuhon in Serat Centini I. The method used in this research is qualitative descriptive, which explores the narrative stories related to the myth of gugon tuhon. The source of data in this study is Serat Centhini 1 by Agus Wahyudi. The data in this study is textual unit related to the form of conveying the myth of gugon tuhon. Data analysis is carried out by understanding in depth analyzing critically, interpreting the available data. The results showed that in Serat Centhini 1 composed by Agus Wahyudi, there is a form of conveying the myth of gugon tuhon through oral and reminder. Both of these tools are important in building public belief and trust in something that must be understood